1968
DOI: 10.1121/1.1910894
|View full text |Cite
|
Sign up to set email alerts
|

The Ear as a Frequency Analyzer. II

Abstract: Previous experiments on the limit of the ear's frequency-analyzing power, carried out with only two subjects, were repeated for four other subjects. The limit was investigated by measuring the number of harmonics of a complex tone that can be heard separately. It was found that, even under the most favorable conditions, not more than the first five to seven harmonics can be distinguished. This limit agrees with the critical-band concept, that is to say, a partial of a multitone stimulus can be heard only when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
1
1

Year Published

1976
1976
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(67 citation statements)
references
References 0 publications
4
59
1
1
Order By: Relevance
“…The upper limit in harmonic number found by Bernstein and Oxenham was markedly higher than found in earlier studies, in which the target harmonic was not pulsed (Plomp, 1964;Plomp and Mimpen, 1968;Soderquist, 1970;Fine and Moore, 1993); these studies generally showed that only the lowest five to eight harmonics could be heard out with 75% or better accuracy. On the other hand, the limit found by Bernstein and Oxenham (2003) corresponds reasonably well with the point above which harmonics produce a less salient pitch, and exhibit other properties (such as phase dependence) that have traditionally been ascribed to unresolved harmonics (Houtsma and Smurzynski, 1990;Shackleton and Carlyon, 1994).…”
Section: Introductioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The upper limit in harmonic number found by Bernstein and Oxenham was markedly higher than found in earlier studies, in which the target harmonic was not pulsed (Plomp, 1964;Plomp and Mimpen, 1968;Soderquist, 1970;Fine and Moore, 1993); these studies generally showed that only the lowest five to eight harmonics could be heard out with 75% or better accuracy. On the other hand, the limit found by Bernstein and Oxenham (2003) corresponds reasonably well with the point above which harmonics produce a less salient pitch, and exhibit other properties (such as phase dependence) that have traditionally been ascribed to unresolved harmonics (Houtsma and Smurzynski, 1990;Shackleton and Carlyon, 1994).…”
Section: Introductioncontrasting
confidence: 65%
“…Partials that can be heard out are often referred to as "resolved," although there are many definitions of what is meant by "resolved" (Moore and Gockel, 2011). The ability to hear out partials depends at least partly on the sharpness of the auditory filters (Plomp, 1964;Plomp and Mimpen, 1968;Moore and Ohgushi, 1993;Moore et al, 2006;Moore and Glasberg, 2011). However, other factors may also play a role.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the pitch of complex tones, most experiments have involved monaural presentation. Plomp (1964) and Plomp and Mimpen (1968) studied the limits of the ear's frequency resolving power and concluded that listeners were able to distinguish the first five to seven harmonics of a complex tone. Smoorenburg (1970) studied pitch perception of complex tones consisting of two components.…”
Section: University Of California San Diegomentioning
confidence: 99%
“…A harmonic template mechanism can only function with resolved harmonics. In humans, the first five to eight harmonics of a complex tone are resolved (Plomp, 1964;Plomp and Mimpen, 1968; but see Bernstein and Oxenham, 2003). Evidence for the existence of harmonic template neurons suitable for extracting pitch is still lacking in the central auditory system (including auditory cortex).…”
Section: Introductionmentioning
confidence: 99%